Riding the South Sea Bubble - Temin, Peter; Voth, Hans-Joachim (American Economic Review, 2004)
This paper presents a case study of a well-informed investor in the South Sea bubble. We argue that Hoare's Bank, a fledgling West End London bank, knew that a bubble was in progress and nonetheless invested in the stock: it was profitable to “ride the bubble.” Using a unique dataset on daily trades, we show that this sophisticated investor was not constrained by such institutional factors as restrictions on short sales or agency problems. Instead, this study demonstrates that predictable investor sentiment can prevent attacks on a bubble; rational investors may attack only when some coordinating event promotes joint action.